L’amour vu comme un « rite de passage » : la confrontation du sacrum et du profanum chez Marguerite Duras - Ledwina, Anna (Quêtes littéraires, 2013)
One of the distinguishing characteristics of Marguerite Duras’ works is her focus on contradictions, especially in the realm of physicality, which is part of the “dialectic of desire”, a nonverbal pleasure. In the analysed novels: The Sea Wall and The Lover this passion manifests itself through the “rite of passage”. It is a double discovery of one’s own and someone else’s physicality. Duras perceives love as an un-controllable, violent “experiment”, a rebellion against one’s mother and restrictions.Narrating one of the most important (and secret) episodes of her life – crossing the Mekong – the author depicts the sexual initiation of a young heroine (Duras’ alter ego), who seduces a mature man with her behaviour and dress. This experience al-lows her to experience the absolute and become initiated and free. For the narrator it is an opportunity for in-depth analysis of the secular and the sacred aspects of desire. To fully understand the sacred and the profane in Duras’ works, it seems necessary to approach the phenomenon from an interdisciplinary perspective.